Resistance of cactus pear (Opuntia ficus-indica) against Pseudocercospora opuntiae through β‑1,3‑glucanase activity and polyphenolic compounds in cladodes - Ochoa, Maria Judith (2019)
Black spot disease, caused by the hemibiotrophic fungus Pseudocercospora opuntiae, is one of the main phytosanitary problems of cactus (Opuntia spp.). Through mass selection, one cultivar of Opuntia ficus-indica (L.) Mill. resistant to colonization by P. opuntiae was identified. The ethanolic extract of resistant cladodes showed higher levels of total condensed tannins, flavonoids and polyphenols than those of the susceptible genotypes, generating 93% inhibition of P. opuntiae conidial germination in vitro. The total protein in the resistant genotype showed 300% higher β-1,3-glucanase than the susceptible genotype. This increased activity was able to inhibit germination of conidia by 90%, a similar effect to that of the fungicide Captan® (N‑trichloromethylthio-4-cyclohexene 1,2-dicarboximide). It was shown, for the first time, that the combined action of cactus polyphenols and β-1,3-glucanase contributes significantly to resistance against P. opuntiae. Activity of this enzyme and the phytochemical profile can be used as criteria to predict and detect cactus germplasm with resistance to black spot.